2022
DOI: 10.1111/aji.13530
|View full text |Cite
|
Sign up to set email alerts
|

Does mRNA SARS‐CoV‐2 vaccine in the follicular fluid impact follicle and oocyte performance in IVF treatments?

Abstract: Problem:The COVID-19 pandemic has many clinical manifestations. Rapid vaccine development raised concerns and speculations about future fertility outcomes and vaccine safety. We evaluated the effect of Pfizer-BioNTech mRNA SARS-CoV-2 vaccine on IVF treatment, oocyte and embryo quality, and pregnancy outcomes. Method of study:This prospective, observational cohort study was conducted in a referral IVF Unit, 3/2021-5/2021. We aimed to recruit all women undergoing IVF/ICSI cycles from 3/1-4/30/2021, 2-8 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 34 publications
(53 reference statements)
2
45
0
1
Order By: Relevance
“…Administration of SARS-CoV-2 vaccine could induce high titers of antigen-specific neutralizing antibodies for CD8 + and Th1 type CD4 + T cells [30]. In addition to serum level changes, anti-SARS-CoV-2 IgG was also detected in the follicular fluid (FF) after vaccination [14,16], suggesting the local involvement of ovary in immune response. More recently, Castiglione Morelli et al [31] found that vaccinated women had higher FF concentrations of Ala and Pro, while levels of lipids, trimethylamine N-oxide and tumor necrosis factor α were lower compared with non-vaccinated control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Administration of SARS-CoV-2 vaccine could induce high titers of antigen-specific neutralizing antibodies for CD8 + and Th1 type CD4 + T cells [30]. In addition to serum level changes, anti-SARS-CoV-2 IgG was also detected in the follicular fluid (FF) after vaccination [14,16], suggesting the local involvement of ovary in immune response. More recently, Castiglione Morelli et al [31] found that vaccinated women had higher FF concentrations of Ala and Pro, while levels of lipids, trimethylamine N-oxide and tumor necrosis factor α were lower compared with non-vaccinated control.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies to date have also assessed the IVF pregnancy outcomes following COVID-19 vaccination, with no significant differences observed in biochemical, clinical or ongoing pregnancy rates [15][16][17][34][35][36]. By analyzing euploid blastocyst transfer cycles, our cohort offers a unique opportunity to investigate independently the possible detrimental effect of vaccine-induced autoimmunity on embryo implantation and pregnancy establishment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] .…”
Section: Uncited Referencesunclassified